Large-Scale Psychological Differences Within China Explained by Rice Versus Wheat Agriculture - Talhelm, T.; Zhang, X.; Oishi, S.; Shimin, C.; Duan, D.; Lan, X.; Kitayama, S. (Science (American Association for the Advancement of Science), 2014)
Cross-cultural psychologists have mostly contrasted East Asia with the West. However, this study shows that there are major psychological differences within China. We propose that a history of farming rice makes cultures more interdependent, whereas farming wheat makes cultures more independent, and these agricultural legacies continue to affect people in the modern world. We tested 1162 Han Chinese participants in six sites and found that rice-growing southern China is more interdependent and holistic-thinking than the wheat-growing north. To control for confounds like climate, we tested people from neighboring counties along the rice-wheat border and found differences that were just as large. We also find that modernization and pathogen prevalence theories do not fit the data.